Does Job Training Work? Causal Evidence of the Kartu Prakerja Program’s Impact on Labor Outcomes - Oktabriyantina, Wulan; Sanjoko, Deny Cahyadinanto (Transpublika Publisher, 2025)
The Indonesian government launched the Kartu Prakerja program to address skill shortages in the labor market, particularly through digital training, with the goal of increasing employability and income levels. This study investigates the impact of Indonesia’s Kartu Prakerja program on workers’ earnings, with a particular focus on the role of digital skills training in enhancing income. Utilizing 2023 Sakernas data and Propensity Score Matching (PSM) to control for selection bias, we find that participation is associated with an average increase in monthly earnings of approximately 3.3%. However, this aggregate effects masks significant heterogeneity. The benefits accrue primarily to lower-middle-income workers, women, urban residents, and formal sector employees. We hypothesize that these groups possess more supportive environments for applying new skills. Conversely, we find no significant effect for the poorest workers, rural residents, and those in informal employment, pointing to structural barriers that prevent them from converting skills into higher wages. These findings are robust to a series of sensitivity checks. In conclusion, while Kartu Prakerja provides measurable benefits, it predominantly assists those already in more advantageous positions, highlighting the need for more targeted designs to achieve equitable income growth.